Evaluation of some physical and chemical properties of the water of the marshes of Dhi Qar Governorate (2017) - A. Mohammed, Najla (Al-Adab Journal, 2019)
The study examined and compared some of the physical and chemical properties of the Marshlands (Chabaish, Abu Zark, Al-Sanaf, Al-Adel) in Dhi Qar Governorate (2017) , The indicators (nitrate ion, dissolved oxygen, phosphate ion) recorded values ​​within the limits allowed for environmental use for drinking, The acid function took the base side and recorded a value within the environmental determinants for irrigation, drinking and animal consumption together, While the index of electrical conductivity was higher than the limits allowed for use (drinking and irrigation together) , And a value higher than the environmentally permissible limits for drinking purposes of indicators (total soluble solids, Total ionization, calcium ion, magnesium ion, ion chlorides other than marsh al-Chabaish, sulfur ions other than Marsh Abu Zirk) , Water specifications when used for irrigation of marshes (Chabaish, Snaaf, Al-Adl) are included in category (C5), which are not suitable for irrigation, And in (C4) in Marsh (Abu Zirk), which is very saline water and is unsuitable for irrigation except for crops with high tolerance to salinity and the soil needs continuous continuous operations and care, The water of marshes (Abu Zirk) is in the category (very good) for animal consumption, and the value of the Marshlands (Chabaish, Alsnaf, Al-Adl) between the category (good, and allowed to use).